Steady-State Error Compensation for Reinforcement Learning-Based Control of Power Electronic Systems - Weber, Daniel; Schenke, Maximilian; Wallscheid, Oliver (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Safe Reinforcement Learning-Based Control in Power Electronic Systems - Weber, Daniel; Schenke, Maximilian; Wallscheid, Oliver (2023 International Conference on Future Energy Solutions (FES))

Ernährungsarmut unter Pandemiebedingungen - Birner, Regina; Linseisen, Jakob; Arens-Azevedo, Ulrike; Balmann, Alfons; Biesalski, Hans Konrad; Bosy-Westphal, Anja; Buyken, Anette; Döring, Thomas; Feindt, Peter; Götz, Kay-Uwe; Iweala, Sarah; Martínez, José; et al. (Berichte über Landwirtschaft)
Ernährungsarmut wird als Problem in Deutschland weitgehend vernachlässigt. Von materieller Ernährungsarmut betroffen sind Menschen, denen es aufgrund fehlender finanzieller Mittel nicht möglich ist, sich gesundheitsfördernd zu ernähren. Etwa 3,5 % der Bevölkerung (rund drei Millionen Menschen) sind durch materielle Ernährungsarmut gefährdet. Damit einher geht oft auch soziale Ernährungsarmut, die Menschen von der sozialen Teilhabe ausschließt, die z. B. durch gemeinsames Essen ermöglicht wird. Essen ist nicht nur von Bedeutung für die körperliche Gesundheit, sondern auch zentral für die psychische Gesundheit und das Wohlbefinden sowie für die soziale Zugehörigkeit, was sich wiederum auf die körperliche Gesundheit auswirkt. Die sozialen Funktionen des Essens werden vielfach übersehen – und bei der Berechnung des Regelbedarfs ausgeblendet. Gerade die Corona-Pandemie hat gezeigt, wie fehlende soziale Kontakte und sozialer Ausschluss sich auf die physische, psychische und soziale Gesundheit auswirken können. Aus Sicht des WBAE (Wissenschaftliche Beirat für Agrarpolitik, Ernährung und gesundheitlichen Verbraucherschutz) ist deshalb der integrative Blick auf die materielle und soziale Ernährungsarmut zentral, da sie sich gegenseitig verstärken können. Diese Stellungnahme befasst sich mit der Frage, wie sich die Corona-Pandemie auf von Ernährungsarmut gefährdete Menschen ausgewirkt hat und was daraus gelernt werden kann. Ein wichtiger Aspekt ist der zeitweilige Wegfall von Essensangeboten in Kitas, Schulen, Tafeln und anderen karitativen Essensangeboten, die ein Sicherheitsnetz für Menschen in Ernährungsarmut darstellen. Die Stellungnahme zieht auf dieser Basis auch Schluss-folgerungen zur Ernährungsarmut außerhalb von Pandemiebedingungen. Im Hinblick auf die Notwendigkeit der Vermeidung von Fehlernährung in Haushalten, die von Ernährungsarmut bedroht sind, kommt der WBAE zu dem Schluss, dass diese Risikogruppe während der Pandemie nicht ausreichend im Fokus der Maßnahmen zur Abmilderung der Pandemiefolgen stand. Dies zeigt sich schon daran, dass kaum Daten erhoben wurden. Deutschland verfügt über kein klares Indikatoren- und Zielsystem und kein Monitoring zur Ernährungsarmut. Die wenigen vorhandenen Daten weisen auf problematische Entwicklungen hin. Insgesamt wurden durch den Bund sehr umfangreiche Mittel zur Bewältigung der wirtschaftlichen und sozialen Folgen der Corona-Pandemie und zur Einkommenssicherung während der Pandemie eingesetzt. Dies ist unter dem Blickwinkel „Ernährungsarmut” positiv zu bewerten. Es ist davon auszugehen, dass diese Maßnahmen verhindert haben, dass noch mehr Haushalte von Ernährungsarmut betroffen waren. Insgesamt zeigt die Analyse jedoch, dass es kaum gezielte Maßnahmen gab, um den Ausfall von Kita- und Schulernährung durch alternative Formen der Bereitstellung von Lebensmitteln oder einer warmen Mahlzeit aufzufangen. Maßnahmen auf Bundesebene fehlten, um Länder, Kommunen und nicht-staatliche Organisationen dabei zu unterstützen. Auswertungen der Pandemiemaßnahmen vergleichbarer Länder zeigen, dass dort schnelle und flexible Maßnahmen zur Bereitstellung von Lebensmitteln eine wichtige Rolle gespielt haben, um armutsgefährdete Haushalte zu unterstützen. In Deutschland wurden vorwiegend finanzielle Transfers genutzt, z. T. zeitlich verzögert und wenig zielgruppenspezifisch. Vor diesem Hintergrund hat der WBAE mögliche Maßnahmen gegen Ernährungsarmut – in Krisen, aber auch generell – untersucht: (1) finanzielle Transfers (einmalig oder fortlaufend), (2) Lebensmittelgutscheine („Voucher“), (3) Lebensmittelpakete und (4) warme Mahlzeiten, wobei die letzten beiden Optionen jeweils zur Abholung oder zur Auslieferung angeboten werden können. Die untersuchten internationalen Beispiele zeigen Möglichkeiten, wie z. T. mit schnellen und teilweise innovativen Ansätzen auf Lockdown-Maßnahmen reagiert wurde. Im Grundsatz spricht aus Sicht des WBAE aber vieles für das deutsche System zur Bekämpfung der Ernährungsarmut, das im Kern auf einem Bürgergeld beruht. Ein solches Bürgergeld muss jedoch ausreichend sein, um materielle und soziale Ernährungsarmut zu vermeiden. Die aktuellen, im Bürgergeld für Essen und Getränke zur Verfügung stehenden Beträge entsprechen allerdings nicht diesem Anspruch. Bei der Einführung des Bürgergelds im Jahr 2023 wurde zwar zeitnah auf die hohe Inflation reagiert. Die Berechnungsmethodik für die Bedarfsermittlung wurde aber nicht angepasst, sodass der Regelsatz nach wie vor nicht für eine gesundheitsfördernde Ernährung ausreicht. Die soziale Funktion von Ernährung wird bei der Berechnung des Regelsatzes nicht berücksichtigt. Um bei akutem Handlungsbedarf, wie z. B. auch bei der derzeitigen Inflation, schneller reagieren zu können, sollten außerdem Systeme zur Auszahlung sozial differenzierter „Krisentransfers” an vulnerable Haushalte mit geringem Verwaltungsaufwand ermöglicht werden. Darüber hinaus sollte für den zentralen Bereich der Kinder-ernährung der Schutz einer adäquaten Grundsicherung durch einen Systemwechsel zu einer integrativen, beitragsfreien und somit nicht-diskriminierenden Kita- und Schulverpflegung ergänzt werden, die zudem den DGE-Qualitätsstandards entspricht. Schließlich sollte der Staat privates, ehrenamtliches Engagement ergänzend fördern, z. B. durch Infrastrukturunterstützung bei karitativen Essensangeboten. Eine Herausforderung der Gestaltung von karitativen Lebensmittelangeboten besteht darin, dass sie oft als stigmatisierend und beschämend wahrgenommen werden und der Nachweis eines Anspruches teils schwierig ist. Zudem bestehen oft nur wenige Wahlmöglichkeiten, sodass individuelle Präferenzen oder Unverträglichkeiten nur sehr eingeschränkt berücksichtigt werden können. Im Hinblick auf die soziale Dimension der Ernährung kommt hinzu, dass wichtige soziale Funktionen des Essens, wie das gemeinsame Essen, also Kommensalität, nicht oder nur sehr eingeschränkt ermöglicht wird. Auch bleiben diejenigen, die versorgt werden, dabei meist unter sich. Vor dem Hintergrund dieser Gesamteinschätzung empfiehlt der WBAE die folgenden, in Abbildung Z 1 dargestellten Maßnahmen (siehe Beitrag). Zusammenfassend betont der WBAE die in Deutschland weiterhin unterschätzten Risiken materieller und sozialer Ernährungsarmut. Im Rahmen der geplanten Nationalen Ernährungsstrategie der Bundesregierung sollte dem Thema Ernährungsarmut aus Sicht des WBAE eine herausgehobene Bedeutung zugemessen werden.

Perspective: A Conceptual Framework for Adaptive Personalized Nutrition Advice Systems - Renner, Britta; Buyken, Anette; Gedrich, Kurt; Lorkowski, Stefan; Watzl, Bernhard; Linseisen, Jakob; Daniel, Hannelore; Conrad, Johanna; Ferrario, Paola G.; Holzapfel, Christina; Leitzmann, Michael; Richter, Margrit; et al. (Advances in Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous); Food Science

CYLENCE: Strategies and Tools for Cross-Media Reporting, Detection, and Treatment of Cyberbullying and Hatespeech in Law Enforcement Agencies - Kaufhold, Marc-André; Bayer, Markus; Bäumler, Julian; Reuter, Christian; Stieglitz, Stefan; Basyurt, Ali Sercan; Mirbabaie, Milad; Fuchß, Christoph; Eyilmez, Kaan (Mensch und Computer)

Improving the End-of-Line Test of Custom-Built Geared Motors using Clustering based on Neural Networks - N., N.

Clifford Embeddings – A Generalized Approach for Embedding in Normed Algebras - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (ECML-PKDD)

Neuro-Symbolic Class Expression Learning - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (International Joint Conference on Artificial Intelligence)

Pairwise Disjoint Perfect Matchings in r-Edge-Connected r-Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (SIAM Journal on Discrete Mathematics)
Keywords: General Mathematics

Das Unterrichtsplanungsprinzip der Interdependenz – Eine netzwerkanalytische Untersuchung der Begründungsstrukturen beim Planungsentscheiden [Einzelbeitrag]. - Scholl, Daniel; Küth, Simon; Vogelsang, Christoph; Meier, Jana; Watson, Christina; Seifert, Andreas

Eine reflexive Haltung als Grundlage einer hochwertigen Unterrichtsreflexion? Zusammenhänge zwischen einer quasi-experimentellen Einstellung zur Reflexion und der Reflexionsperformanz von Lehramtsstudierenden [Einzelbeitrag]. - Scholl, Daniel; Vogelsang, Christoph; Küth, Simon; Meier, Jana; Watson, Christina; Seifert, Andreas

Advanced Synchronous Rectification for an IGBT-Based ZCS LLC Converter with High Output Currents for a 2 kW Automotive DC-DC Stage - Urbaneck, Daniel; Schafmeister, Frank; Böcker, Joachim (PCIM Europe 2023)
State-of-the-art LLC resonant converters use MOSFETs in their inverter stage, which allows high switching frequencies and thus the use of compact magnetic components. The large parasitic output capacitance and the poor reverse-recovery behaviour of the inherent body diode of high-voltage (600 V) silicon MOSFETs require soft switching, i.e. zero-voltage switching (ZVS). Otherwise, the high turn-on switching losses would lead to excessive heating and ultimately to the destruction of the switch. Therefore, MOSFET-based LLC converters are operated in the so-called inductive region only, which enables ZVS. The use of robust and cost-effective IGBTs instead of MOSFETs is particularly advantageous for automotive applications, since in addition to high reliability low costs are an important objective here. Since IGBTs are characterized by dominant turn-off losses and generally higher switching losses compared to MOSFETs, the aim is to operate them with zero-current switching (ZCS) and at low switching frequencies below the resonance frequency. In this region also the voltage transfer characteristic is steeper, which qualifies for applications with a strongly varying input-to-output voltage ratio, such as given for automotive on-board DC-DC converters connecting the (high-voltage) traction battery with the (12 V) auxiliary battery. In this paper, a stress value analysis based on a switched-model simulation is used to design a ZCS LLC converter and take advantage of the mentioned benefits of IGBTs as well as of the steeper voltage transfer characteristic. Within this operation region below the resonance frequency, however, a new phenomenon of several current pulses occurring during a single switching period through the rectifier components may appear. Generally, in applications with high output currents a synchronous rectifier (SR) is often used to keep the conduction losses of the rectifier stage at a moderate level: Low-voltage MOSFETs, which actively need to be gated synchronously to the polarity of the current pulses, are employed then instead of more lossy rectifier diodes. However, standard SR driver ICs have been shown to be unable to properly rectify the multi-pulse output currents of the proposed LLC operation, resulting in high conduction losses of the rectifier stage. A cost-effective hardware concept is presented which ensures proper rectification by using standard SR-ICs that are actively overdriven by the converter’s central microcontroller. A 2 kW prototype for an EV on-board DC-DC converter was built to show the effectiveness of the method, documenting an increase in efficiency by up to 4.1 % compared to a purely SR-IC-based solution. Overall efficiency is very similar to that of a conventional (MOSFET-based) LLC converter so that the ZCS-operated LLC IGBT-converter represents a cost-effective alternative, which even shows 10 % less worst-case losses.
Keywords: LLC Converter; IGBT; ZCS; Synchronous Rectification

Computing and Compressing Electron Repulsion Integrals on FPGAs - Wu, Xin; Kenter, Tobias; Schade, Robert; Kühne, Thomas; Plessl, Christian (2023 IEEE 31st Annual International Symposium on Field-Programmable Custom Computing Machines (FCCM))
The computation of electron repulsion integrals (ERIs) over Gaussian-type orbitals (GTOs) is a challenging problem in quantum-mechanics-based atomistic simulations. In practical simulations, several trillions of ERIs may have to be computed for every time step. In this work, we investigate FPGAs as accelerators for the ERI computation. We use template parameters, here within the Intel oneAPI tool flow, to create customized designs for 256 different ERI quartet classes, based on their orbitals. To maximize data reuse, all intermediates are buffered in FPGA on-chip memory with customized layout. The pre-calculation of intermediates also helps to overcome data dependencies caused by multi-dimensional recurrence relations. The involved loop structures are partially or even fully unrolled for high throughput of FPGA kernels. Furthermore, a lossy compression algorithm utilizing arbitrary bitwidth integers is integrated in the FPGA kernels. To our best knowledge, this is the first work on ERI computation on FPGAs that supports more than just the single most basic quartet class. Also, the integration of ERI computation and compression it a novelty that is not even covered by CPU or GPU libraries so far. Our evaluation shows that using 16-bit integer for the ERI compression, the fastest FPGA kernels exceed the performance of 10 GERIS ($10 × 10^9$ ERIs per second) on one Intel Stratix 10 GX 2800 FPGA, with maximum absolute errors around $10^{-7}$ - $10^{-5}$ Hartree. The measured throughput can be accurately explained by a performance model. The FPGA kernels deployed on 2 FPGAs outperform similar computations using the widely used libint reference on a two-socket server with 40 Xeon Gold 6148 CPU cores of the same process technology by factors up to 6.0x and on a new two-socket server with 128 EPYC 7713 CPU cores by up to 1.9x.

Breaking the exascale barrier for the electronic structure problem in ab-initio molecular dynamics - Schade, Robert; Kenter, Tobias; Elgabarty, Hossam; Lass, Michael; Kühne, Thomas; Plessl, Christian (The International Journal of High Performance Computing Applications)
The non-orthogonal local submatrix method applied to electronic structure–based molecular dynamics simulations is shown to exceed 1.1 EFLOP/s in FP16/FP32-mixed floating-point arithmetic when using 4400 NVIDIA A100 GPUs of the Perlmutter system. This is enabled by a modification of the original method that pushes the sustained fraction of the peak performance to about 80%. Example calculations are performed for SARS-CoV-2 spike proteins with up to 83 million atoms.
Keywords: Hardware and Architecture; Theoretical Computer Science; Software

Modeling of Masked Droplet Deposition for Site-Controlled Ga Droplets - Feddersen, Stefan; Zolatanosha, Viktoryia; Alshaikh, Ahmed; Reuter, Dirk; Heyn, Christian (Nanomaterials)
Site-controlled Ga droplets on AlGaAs substrates are fabricated using area-selective deposition of Ga through apertures in a mask during molecular beam epitaxy (MBE). The Ga droplets can be crystallized into GaAs quantum dots using a crystallization step under As flux. In order to model the complex process, including the masked deposition of the droplets and a reduction of their number during a thermal annealing step, a multiscale kinetic Monte Carlo (mkMC) simulation of self-assembled Ga droplet formation on AlGaAs is expanded for area-selective deposition. The simulation has only two free model parameters: the activation energy for surface diffusion and the activation energy for thermal escape of adatoms from a droplet. Simulated droplet numbers within the opening of the aperture agree quantitatively with the experimental results down to the perfect site-control, with one droplet per aperture. However, the model parameters are different compared to those of the self-assembled droplet growth. We attribute this to the presence of the mask in close proximity to the surface, which modifies the local process temperature and the As background. This approach also explains the dependence of the model parameters on the size of the aperture.
Keywords: General Materials Science; General Chemical Engineering

Dispersion Energy‐Stabilized Boron and Phosphorus Lewis Pairs - Sieland, Benedikt; Stahn, Marcel; Schoch, Roland; Daniliuc, Constantin; Spicher, Sebastian; Grimme, Stefan; Hansen, Andreas; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

"Tankrabatt" und "Freiheitsenergie". Wie der Blog "neusprech.org" politische Euphemismen entlarvt - Tophinke, Doris (Zwischen Fake und Fakt)

Annotation uncertainty in the context of grammatical change - Merten, Marie-Luis; Wever, Marcel; Tophinke, Doris; Geierhos, Michaela; Hüllermeier, Eyke (International Journal of Corpus Linguistics)

Advanced Algorithm Selection with Machine Learning: Handling Large Algorithm Sets, Learning From Censored Data, and Simplyfing Meta Level Decisions - Tornede, Alexander

Information Asymmetry and Gendered Behavior in Organizations and Digital Markets - Spiess-Bru, Clarissa